Attitudes of College Undergraduates Towards Coyotes (Canis latrans) in an Urban Landscape: Management and Public Outreach Implications - Megan M. Draheim; Katheryn W. Patterson; Larry L. Rockwood; Gregory A. Guagnano; E. Christien M. Parsons (Animals, 2013)
Understanding and assessing the public’s attitudes towards urban wildlife is an important step towards creating management plans, increasing knowledge and awareness, and fostering coexistence between people and wildlife. We conducted a survey of undergraduate college students in the Washington, D.C. metropolitan area—where coyotes are recent arrivals—to determine existing attitudes towards coyotes and coyote management methods. Amongst other findings, we found that the more a person feared coyotes, the less likely they were to support their presence (p < 0.001), and the less likely they were to believe that pet owners should be directly responsible for protecting their pets (p < 0.001). Respondents demonstrated major gaps in their understanding of basic coyote biology and ecology. Respondents broke wildlife management practices into two categories: those that involved an action on coyotes (both lethal or non-lethal; referred to as “Coyote”), and those that restricted human behavior (referred to as “Human”); the “Human” methods were preferred. We found important differences between key demographic groups in terms of attitudes and management preferences. Our study suggests that wildlife professionals have unique opportunities in urban areas to prevent and reduce conflict before it escalates, in part by targeting tailored outreach messages to various demographic and social groups.